2004
DOI: 10.1101/lm.70704
|View full text |Cite
|
Sign up to set email alerts
|

Pavlovian Conditioning ofHermissenda: Current Cellular, Molecular, and Circuit Perspectives

Abstract: The less-complex central nervous system of many invertebrates make them attractive for not only the molecular analysis of the associative learning and memory, but also in determining how neural circuits are modified by learning to generate changes in behavior. The nudibranch mollusk Hermissenda crassicornis is a preparation that has contributed to an understanding of cellular and molecular mechanisms of Pavlovian conditioning. Identified neurons in the conditioned stimulus (CS) pathway have been studied in det… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
52
0

Year Published

2006
2006
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 71 publications
(53 citation statements)
references
References 112 publications
(175 reference statements)
0
52
0
Order By: Relevance
“…A good deal is known about the cellular mechanisms of an associative form of learning, classical conditioning, as well as nonassociative forms of learning of several invertebrate behaviors (Hawkins et al, 1987;Benjamin et al, 2000;Burrell and Sahley, 2001;Menzel, 2001;Roman and Davis, 2001;Crow, 2004), including the gill-and siphon-withdrawal reflex in Aplysia (Hawkins et al, 1993;Antonov et al, 2001Antonov et al, , 2003Roberts and Glanzman, 2003). In recent years, there also has been progress in understanding mechanisms of another associative form of learning, operant conditioning, in invertebrates (Brembs, 2003), allowing comparisons with mechanisms of both classical conditioning and nonassociative forms of learning.…”
Section: Discussionmentioning
confidence: 99%
“…A good deal is known about the cellular mechanisms of an associative form of learning, classical conditioning, as well as nonassociative forms of learning of several invertebrate behaviors (Hawkins et al, 1987;Benjamin et al, 2000;Burrell and Sahley, 2001;Menzel, 2001;Roman and Davis, 2001;Crow, 2004), including the gill-and siphon-withdrawal reflex in Aplysia (Hawkins et al, 1993;Antonov et al, 2001Antonov et al, , 2003Roberts and Glanzman, 2003). In recent years, there also has been progress in understanding mechanisms of another associative form of learning, operant conditioning, in invertebrates (Brembs, 2003), allowing comparisons with mechanisms of both classical conditioning and nonassociative forms of learning.…”
Section: Discussionmentioning
confidence: 99%
“…The conditioning procedure consists of pairing light CS with high-speed rotation, or orbital shaking (US) which are aversive stimuli for the snail (Crow, 2004). Two responses are elicited by rotation, a reduced rate of forward locomotion and foot shortening.…”
Section: Invertebrate Classical Conditioningmentioning
confidence: 99%
“…Alternatively, existing synapses may be nonfunctional or too weak to mediate a strong effect on feeding activity in naive animals before conditioning. Strengthening of weak synapses has been demonstrated to underlie various conditioning paradigms (Kandel and Schwartz, 1982;Glanzman, 1995;Hawkins et al, 1998;Antonov et al, 2003;Roberts and Glanzman, 2003;Wickens et al, 2003;Crow, 2004), whereas the activation of silent synapses has been suggested to contribute to long-term potentiation (Montgomery et al, 2001;Voronin and Cherubini, 2004). Regardless of the underlying mechanism, our results suggest that conditioning leads to the creation of a functionally new pathway, probably attributable to the enhanced recruitment of CBIs to the CS processing pathway, which enables the CS to activate feeding after conditioning.…”
Section: Discussionmentioning
confidence: 52%